Triple Viral Infections in Advanced Breast Cancer: Insights from a Three-Case Report and Literature Review - Ashraf I. Khasawneh; Nisreen Himsawi; Mohammed Alorjani; Hadeel Al-Momani; Uruk Shahin; Ashraf Sammour; Tareq Saleh; Hafez Al-Momani; Rame Khasawneh; Sofian Al Shboul (Diagnostics)
Background and clinical significance: Viral infections are typically considered contributing or secondary factors in the development of breast cancer. Case presentation: This case report presents three instances of advanced breast cancer associated with triple viral infections. Case 1 involves a 78-year-old woman diagnosed with grade 2 invasive ductal carcinoma positive for HPV-18, CMV, and BLV. Case 2 describes a 39-year-old woman with grade 2 invasive ductal carcinoma, positive for HPV-16, CMV, and BLV. Case 3 is a 52-year-old woman with grade 3 invasive ductal carcinoma, positive for HPV-16, BLV, and MMTV. These cases suggest a possible correlation between viral co-infections and breast cancer aggressiveness, posing new questions about the role of viral infections in cancer development and prognosis. Conclusions: The findings contribute to growing evidence that viral infections may influence the progression and therapeutic response of breast cancer, warranting further investigation into targeted preventive measures including vaccinations.